2011
DOI: 10.1007/s00125-011-2153-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor (EGF)-receptor signalling is needed for murine beta cell mass expansion in response to high-fat diet and pregnancy but not after pancreatic duct ligation

Abstract: Aims/hypothesis Epidermal growth factor receptor (EGFR) signalling is essential for the proper fetal development of pancreatic islets and in the postnatal formation of an adequate beta cell mass. In this study we investigated the role of EGFR signalling in the physiological states of beta cell mass expansion in adults during metabolic syndrome and pregnancy, as well as in regeneration after pancreatic duct ligation. Methods Heterozygous Pdx1-EGFR-dominant-negative (E1-DN) mice, which have a kinase-negative EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 53 publications
0
58
0
1
Order By: Relevance
“…First, MSC R showed increased secretion of EGF previously shown to increase beta cell mass in rodents by stimulating beta cell replication [42]. However, EGF receptor signalling was required for expansion of murine beta cell mass in response to a high-fat diet, but was not crucial for neoislet formation after pancreatic ductal ligation [43]. Second, the CCN family of extracellular matrix-associated, heparin-binding proteins has been shown to modulate cell growth and repair in many tissues by increasing the bioavailability of BMPs, VEGF, Wnt and TGF ligands [44].…”
Section: Discussionmentioning
confidence: 99%
“…First, MSC R showed increased secretion of EGF previously shown to increase beta cell mass in rodents by stimulating beta cell replication [42]. However, EGF receptor signalling was required for expansion of murine beta cell mass in response to a high-fat diet, but was not crucial for neoislet formation after pancreatic ductal ligation [43]. Second, the CCN family of extracellular matrix-associated, heparin-binding proteins has been shown to modulate cell growth and repair in many tissues by increasing the bioavailability of BMPs, VEGF, Wnt and TGF ligands [44].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling pathways are essential for ␤-cell mass expansion in response to a high-fat diet and in pregnancy (200). EGF is synthesized in the pancreas and increases insulin secretion in mouse pancreatic islets; EGF expression levels are decreased in diabetic animals (285).…”
Section: A Egfr Signaling and Diabetesmentioning
confidence: 99%
“…In 2004, another independent group revealed that β-cell proliferation is the primary mechanism for maintaining postnatal β-cell mass in mice 42 . Subsequently, numerous studies demonstrated using animal models of β-cell ablation, insulin resistance, high fat diet/obesity and pregnancy that β-cell proliferation is a major mechanism for restoring adequate β-cell mass resulting in maintenance of normal glucose homeostasis in both pathological and physiological conditions 2 - 5 , 43 , 44 . However, knowledge of human β-cell proliferation was obscure until an elegant study published in 2008 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our studies have revealed that siRNA-mediated downregulation of p27(Kip1) along with either of the GSK-3 isoforms does not stimulate INS-1 cell proliferation any further relative to individual knockdown of each of the GSK-3 isoforms, indicating GSK-3 as an upstream modulator of p27(Kip1) in β-cells. Studies have shown that adaptive growth of β-cell mass occurs via increased proliferation of β-cells for compensating elevated insulin demand during pregnancy and also, in response to high fat diet/obesity 43 , 44 , 51 . Studies have also demonstrated that decreased levels of p27(Kip1) and p18(Ink4c) are required for increased β-cell proliferation during pregnancy and hyperphagic obesity 51 .…”
Section: Discussionmentioning
confidence: 99%